The Use of Covid-19 Personal Protective Equipment with Nurse's Work Stress In The Hospital - Siti Latipah; Shieva Nur Azizah Ahmad; Ria Nur Fiana (Universitas Aisyah Pringsewu, 2023)
The world is facing a major public health crisis due to the Covid-19 disease. This virus spread rapidly throughout the world, including in Indonesia. In the current pandemic era, nurses must use Covid-19 personal protective equipment (PPE) in full and according to the standards for using Covid-19 personal protective equipment (PPE). This research is a correlational study with a cross-sectional approach. The population of this study is all nurses at the Kalideres Private Hospital who are currently treating COVID-19 patients, totaling 110 nurses. Sampling using the Proportionate Stratified Random Sampling technique. The number of respondents was 87 nurses. The time of this research is September 2021. Data analysis with chi-square test. The results showed that the p-value was 0.001 less than 0.05. There is a relationship between the use of Covid-19 personal protective equipment (PPE) and nurses' work stress level. This research is expected to improve PPE's safety and security standards in working, especially in hospitals, and can prevent work stress on nurses. Abstrak: Dunia saat ini sedang menghadapi krisis kesehatan masyarakat yang besar akibat penyakit Covid-19. Virus ini menyebar dengan cepat ke seluruh dunia termasuk Indonesia. Di era pandemi saat ini perawat diharuskan menggunakan alat pelindung diri (APD) Covid-19 secara lengkap dan sesuai standar pemakaian alat pelindung diri (APD) Covid-19. Penelitian ini adalah penelitian korelasional dengan pendekatan cross sectional. Populasi penelitian ini adalah seluruh perawat yang ada di Rumah Sakit Swasta Kalideres yang saat ini menangani pasien COVID-19 yang berjumlah 110 perawat.Pengambilan sampel dengan teknik Proportionate Stratified Random Sampling. Jumlah responden 87 perawat. Waktu penelitian ini September 2021. Analisa data dengan uji chi square. Hasil penelitian menunjukkan nilai p-value 0.001 kurang dari 0.05. Ada hubungan penggunaan alat pelindung diri (APD) Covid-19 dengan tingkat stress kerja perawat. Penelitian ini diharapkan dapat meningkatkan standar keamanan dan keselamatan APD dalam bekerja khususnya di RS, dan dapat mencegah stress kerja pada perawat.